Avaliação morfológica em podócitos de pacientes com podocitopatias - SILVA, Crislaine Aparecida da (2019)
Introduction: Focal segmental glomerulosclerosis (FSGS) and minimal change disease (MCD) are among the main causes of idiopathic nephrotic syndrome. Podocyte injury results from the imbalance between adaptive responses that maintain homeostasis and cellular dysfunction that can culminate in cell death. Therefore, an in situ analysis was performed to detect morphological changes related to cell death and autophagy in renal biopsies from adult patients with podocytopathies. Methods: A total of 49 renal biopsies from patients diagnosed with FSGS (n = 22) and MCD (n = 27) were selected. In situ expression of Wilms Tumor 1 protein (WT1), light chain microtubule 1-associated protein (LC3) and caspase-3 protein were evaluated by immunohistochemistry. The foot process effacement and morphological alterations related to podocyte cell death and autophagy were analyzed with transmission electron microscopy. Results: A reduction in the density of WT1-labeled podocytes was observed for FSGS and MCD cases as compared to controls. Foot process width in FSGS was significantly larger compared to MCD and correlated with proteinuria. A density of LC3-labeled podocytes and the number of autophagosomes in podocytes/ pedicels were higher in the DLM group than in the GESF group. In addition, the number of autophagosomes correlated positively with the estimated glomerular filtration rate in cases of DLM. The density of caspase-3-labeled podocytes in FSGS and MCD was higher than control group, and a higher number of podocytes with an evidence of necrosis was detected in FSGS cases than in MCD cases. Conclusion: Podocytes from patients diagnosed with FSGS showed more morphological and functional alterations resulting from a larger number of lesions and reduced cell adaptation.